Peripheral viral challenge elevates extracellular glutamate in the hippocampus leading to seizure hypersusceptibility. Issue 3 (27th March 2017) - Hunsberger, Holly C.; Konat, Gregory W.; Reed, Miranda N.
Abstract: Peripheral viral infections increase seizure propensity and intensity in susceptible individuals. We have modeled this comorbidity by demonstrating that the acute phase response instigated by an intraperitoneal (i.p.) injection of a viral mimetic, polyinosinic‐polycytidylic acid (PIC), induces protracted hypersusceptibility to kainic acid‐induced seizures. We have further demonstrated that PIC challenge robustly increases the level of tonic extracellular glutamate and neuronal excitability in the hippocampus. This study was undertaken to determine a relationship between tonic glutamate and seizure susceptibility following PIC challenge. Briefly, glutamate‐sensing microelectrodes were permanently implanted into the CA1 of 8‐week‐old female C57BL/6 mice. Following a 3‐day recovery, acute phase response was induced by i.p. injection of 12 mg/kg of PIC, while saline‐injected mice served as controls. Tonic glutamate was measured at 1, 2, 3 and 4 days after PIC challenge. PIC challenge induced an approximately fourfold increase in tonic glutamate levels measured after 24 h. The levels gradually declined to the baseline values within 4 days. Twenty‐four hours after PIC challenge, the mice featured an approximately threefold increase in cumulative seizure scores and twofold increase in the duration of status epilepticus induced by subcutaneous injection of 12 mg/kg of kainic acid. Seizure scores positively correlated with pre‐seizure tonic glutamate. Moreover, seizures resulted in a profound (76%) elevation of extracellular glutamate in the CA1 of PIC‐challenged but not saline‐injected mice. Our results implicate the increase in extracellular glutamate as a mediator of seizure hypersusceptibility induced by peripheral viral challenge. Abstract : Intraperitoneal injection of a viral mimetic, polyinosinic‐polycytidylic acid (PIC), results in a robust elevation of extracellular (tonic) glutamate in the hippocampus. Here, we showed that tonic glutamate levels positively correlate with the susceptibility to kainic acid (KA)‐induced seizures. The elevation of tonic glutamate by PIC challenge likely results from the hyperexcitability of hippocampal neurons. In addition, tonic glutamate level might be increased directly by inflammatory milieu in the hippocampal parenchyma. Tonic glutamate enhances and/or sustains neuronal excitability likely through extrasynaptic receptors. We posit that both, neuronal hyperexcitability and elevated tonic glutamate contribute to the exacerbation of seizure susceptibility.